Analisis Faktor-Faktor Yang Berhubungan Dengan Pengetahuan Perawat Tentang Pencegahan Ventilator Associated Pneumonia (VAP) Di Ruang ICU RSUD Dr. Moewardi - Akhmad Rifai ((JKG) Jurnal Keperawatan Global, 2016)
Abstract : Knowledge, Ventilator Associated Pneumonia (VAP). The use of mechanical ventilators often cause problems, such as lung infections, like pneumonia. The fact of the Center for Disesase Control (CDC), namely the prevention of Hospital Acquire Pneumonia (HAP) that most of the procedures to prevent VAP conducted by nurses. Nurses should have knowledge of how prevention of VAP. Where knowledge is influenced by several factors, including internal and external factors. The purpose of this study was to determine the factors associated with nurse’s knowledge on the prevention of Ventilator Associated Pneumonia (VAP) in ICU of RSUD Dr. Moewardi Surakarta. The study was descriptive correlational with cross sectional approach. The results of this research indicate that there is no relationship between education with the knowledge of nurses on the preventing of VAP evidenced by the r value of -0.036 count is smaller than r table 0.4005. There was no relationship between years of service with the knowledge of nurses on the preventing of VAP evidenced by the r value of 0.026 count is smaller than r table 0.4005. There was no relationship between training with the knowledge of nurses on the preventing of VAP evidenced by the r value of -0.312 count is smaller than r table 0.4005. There was no relationship between education, years of service, and training with the knowledge of nurses on the preventing of VAP.